(3GQJTGa GdVQH ef dSGf GdYQHs - (3eMeO Hf jhSa Hf Ydj Hf jhSa GHf nMnqjGf GdZQfGWj GdCfOdSj GdLjGfj, GdpqfraRj, CKjQ GdOjf, CHh MjGf,J (B745 (3g` s ((3HdGO GdgfO s)
(3ChdgG (B:s
(3hHYO, aEf Yde GdfMh UYH GdeQGe, eSJYUj Ydi GdCagGe dG jfaP aj eYQaJg EdG GdPgf GdSdje s
(3BNQgG (B:s
(3bGd GdCSJGP CHhHcQ Hf WGgQ(B: (3gPG GSe Yde cCSGeI JeJ GdcJGH s
(3fSNI QGHYI JJab aj ChdgG eY GdfSNI GdChdi HGNJdGa jSjQ aj HYV GdCdaGXs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B152 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B130s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B14 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B61s
Keywords: (3GdfMhs